The Collateral Framework of the Eurosystem and Its Fiscal Implications - Jakob Korbinian Eberl (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
This thesis was written by Jakob Eberl while having been a research assistant at the Center for Economic Studies (CES) at the University of Munich. It was completed in December 2015 and accepted as a doctoral thesis by the Department of Economics at the University of Munich in May 2016. The thesis tells the story of the Eurosystem's collateral framework and its fiscal implications in seven chapters (neglecting the introduction and the conclusion), which can be conceptually assigned to two parts.
Keywords: E51; E52; E58; E62; E63; H12; H63; H77; H81; 330; Zentralbank; Geldpolitik; Finanzpolitik; Euromarkt; Kreditsicherung; Repo-Geschäft; Eurozone